Pengaruh Terpaan Ads Instagram dan Harga terhadap Keputusan Pembelian Produk Nitro Ventura - Prasetiyo, Budi; Azura, Amberia Narfi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: The aim of this study is to determine whether the price effect on purchasing decisions exists, to determine your options regarding purchasing products at Nitro Ventura, and to determine the influence of advertising on Instagram on the decision to buy nitro-ventura goods. Research Methodology: The place where the research was conducted was the Nitro Ventura Coffee Shop, Bandung. The data used is primary data which the author took from data from Moka Pos Nitro Ventura and its Instagram followers. The sampling technique used a non-probability sampling technique with a judgment sampling method. The sample size was calculated using the Slovin formula to obtain the required sample of 88 respondents. The analysis technique used in this research is multiple linear regression analysis, with hypothesis testing using the t test and f test, as well as the coefficient of determination Results: Normal, Heteroscedasticity test: No multicollinearity occurred Partial Influence: Instagram Ads have greater influence (44.88%) Rsquare: 66.5% Limitations: Short Term Effects, External Factors Contribution: This research can be especially useful for the Nitro Ventura Coffee Shop and students conducting research on this topic.